2019
DOI: 10.1093/jee/toz019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hypoxia Against Tribolium castaneum (Coleoptera: Tenebrionidae) Throughout Ontogeny

Abstract: Hermetic grain storage technology offers a viable chemical-free approach to control storage insects. However, there is limited knowledge on how hypoxia affects the survival of insect life stages during grain storage in hermetic bags. We exposed Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) eggs (2 d), young larvae (7 d), old larvae (21 d), pupae (28 d), and adults (2 d after emergence) to 2, 4, 8, and 20.9% oxygen levels for 1, 3, 5, 10, and 15 d and assessed subsequent mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…Assessment immediately after exposure to hypoxia treatments for 14 d revealed no adult S. oryzae survived. These findings are in agreement with results of Kharel et al (2019) who showed that exposure of T. castaneum to 2% or less for 15 d resulted in no adult survival. However, exposure to higher oxygen levels such as 4 and 8% did not result in complete mortality.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Assessment immediately after exposure to hypoxia treatments for 14 d revealed no adult S. oryzae survived. These findings are in agreement with results of Kharel et al (2019) who showed that exposure of T. castaneum to 2% or less for 15 d resulted in no adult survival. However, exposure to higher oxygen levels such as 4 and 8% did not result in complete mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results showed no adult emergence from 1% oxygen level after 45 d post-treatment. This result corroborates previous findings that show exposure of C. maculatus and T. castaneum eggs to oxygen levels below 2% causes up to 100% egg mortality (Cheng et al 2012, Kharel et al 2019). Though 3 and 5% resulted in a few live adults 45 d post-treatment, they might have affected the development of the insects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As documented for many species from different orders, insects achieve extraordinary resistance to hypoxia by switching to anaerobic metabolic pathways and reduction of basal metabolic rates amongst other adaptations (reviewed by Hoback and Stanley, 2001). Hypoxia tolerance has also been reported for locusts (Arieli and Lehrer, 1988; Wegener and Moratzky, 1995; Greenlee and Harrison, 2004) and T. castaneum (Donahaye, 1990; Kharel et al, 2019), the two species in which CRLF3-mediated neuroprotection has been demonstrated. In comparison to mammalian neurons, where rather brief hypoxic episodes are sufficient to induce apoptosis, survival of locust and beetle neurons in vitro decreases only 20–30% even when challenged by prolonged (36 h) and severe (<0.3% oxygen) hypoxia (this study; Miljus et al, 2014; Hahn et al, 2017).…”
Section: Discussionmentioning
confidence: 80%